Draft Genome Sequence of Enteropathogenic Escherichia coli, Isolated from the Bloody Stool Sample of a Common Marmoset (Callithrix jacchus) - Hayashimoto, Nobuhito (Genome Announc, 2015)
Here, we report the draft genome sequence of Escherichia coli strain R811. This bacterium was isolated from the bloody stool sample of a common marmoset, and was categorized as enteropathogenic E. coli because it possessed eae.